2000
DOI: 10.1159/000018860
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Leiomyomatosis in a Woman with a History of Vulvar Leiomyoma and Barrett’s Esophagus

Abstract: Background: The diagnosis and treatment of esophageal pathology remains a challenge despite advances in preoperative endoscopy, radiographic staging, and perioperative care. Case Report: In this article, we present an interesting case of esophageal leiomyomatosis in a woman with a history of vulvar leiomyoma and Barrett’s esophagus. This paper represents the first reported simultaneous occurrence of these three pathologic entities in the English literature. Conclusions: The clinical presentation and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(7 reference statements)
2
4
0
Order By: Relevance
“…Additionally, esophagoscopy can only show acute esophagitis and barett esophagus [Nahmad and Clatworthy, 1973;Leborgne et al, 1989;Compagnoni et al, 2000], again also documented in our patient. Muscular hypertrophy always affects the esophagus but may as well involve extraesophageal organs like the tracheobronchial [Leborgne et al, 1989;Antignac and Heidet, 1996] and female genital tracts [Compagnoni et al, 2000;Guillem et al, 2001]. Guthrie [1945] described a 9-year-old girl with involvement of the esophagus, pylorus, duodenum, and jejunum.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, esophagoscopy can only show acute esophagitis and barett esophagus [Nahmad and Clatworthy, 1973;Leborgne et al, 1989;Compagnoni et al, 2000], again also documented in our patient. Muscular hypertrophy always affects the esophagus but may as well involve extraesophageal organs like the tracheobronchial [Leborgne et al, 1989;Antignac and Heidet, 1996] and female genital tracts [Compagnoni et al, 2000;Guillem et al, 2001]. Guthrie [1945] described a 9-year-old girl with involvement of the esophagus, pylorus, duodenum, and jejunum.…”
Section: Discussionsupporting
confidence: 77%
“…Combined leiomyoma of the vulva and oesophagus is even rarer, with only 21 cases reported 3,4 . Some cases were leiomyomatosis where there was diffuse smooth muscle hypertrophy 3,4 or multiple nodules 5 rather than a discrete tumour. Our tumour was macroscopically discrete but had nodules histopathologically.…”
Section: Discussionmentioning
confidence: 99%
“…Our tumour was macroscopically discrete but had nodules histopathologically. It has been suggested that these cases represented an ‘esophago‐vulvar’ syndrome 3 …”
Section: Discussionmentioning
confidence: 99%
“…Rarely, thickened layers of the esophageal wall can also be caused by diffuse leiomyomatosis, a benign muscular abnormality (1). Diffuse leiomyomatosis is also known as giant muscular hypertrophy with diffuse proliferation of the esophageal smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse esophageal leiomyomatosis is a rare benign disease of proliferating smooth muscle that can be accompanied by leiomyoma of extraesophageal organs including the tracheobronchial and genital tracts (1-3). Moreover, diffuse leiomyomatosis can be associated with Alport syndrome in familial cases (2, 4).…”
mentioning
confidence: 99%